Seismic Energy Assessment of Buildings with Tuned Vibration Absorbers - Said Elias (Shock and Vibration)
Seismic analysis and energy assessment of building installed with distributed tuned vibration absorbers (d-TVAs) are presented. The performance of d-TVAs is compared with single tuned vibration absorber (STVA) installed at the top of the building. The placements of the d-TVAs are based on the modal properties of the uncontrolled and controlled buildings. The governing equations of motion of the building with the STVA and d-TVAs are solved by employing Newmark’s integration method. Various energies under earthquake ground excitations are computed to study the effectiveness of using the STVA and d-TVAs. It is concluded that the use of the d-TVAs is the most competent because it effectively dissipates the seismic energy, and they are convenient to install requiring reduced space, as are placed at various floors.